Design, synthesis and biological evaluation of potent EGFR kinase inhibitors against 19D/T790M/C797S mutation. Issue 16 (15th August 2020) - Su, Zhicheng; Yang, Tingyuan; Wang, Jie; Lai, Mengzhen; Tong, Linjiang; Wumaier, Gulinuer; Chen, Zhuo; Li, Shengqing; Li, Honglin; Xie, Hua; Zhao, Zhenjiang
Graphical abstract: Abstract: The efficacy of EGFR inhibitors is frequently affected by acquired resistance. EGFR 19D/T790M/C797S mutation is one of the primary reasons for the emergence of resistance after treatment with the third-generation EGFR inhibitors such as AZD9291, CO1686 and Olmutinib. To overcome the resistance mutation 19D/T790M/C797S, we designed and prepared a series of indole derivatives with the terminal hydroxyl of alkyl chain to increase extra interaction with the Asp855 in the conservative DFG site. Activity evaluation, structure-activity relationship and docking analysis were also carried out. Among them, compound 12e displayed significant inhibitory activity against EGFR 19D/T790M/C797S (IC50 = 15.3 nM) and good selectivity over EGFR WT (IC50 > 1000 nM), L858R/T790M (IC50, 156.6 nM) and L858R/T790M/C797S (IC50, 218.3 nM) respectively. Furthermore, 12e exhibited good growth inhibition activity, induced G1 phase cell cycle arrest and apoptosis in BaF3/EGFR 19D/T790M/C797S cells by suppressing EGFR phosphorylation signaling pathway. In all, our study might provide a novel structural design method and lay the solid foundation for the development of the 4th generation EGFR 19D/T790M/C797S inhibitors.